The Role of Place, Geography, and Geographic Information Systems in Educational Research. (August 2019) - Mann, Bryan; Saultz, Andrew
Despite the strong relationship between geography and education policy, educational research tends to draw from other fields of inquiry such as economics, political science, and history. This special topics collection centers the usefulness of geography and place in educational policy research. The introduction explains the rationale for the collection and discusses the themes and articles in the collection. We conclude with a call for researchers, policy makers, and colleges of education to enhance their capacity in incorporating geographic thinking into educational policy research.